Sustaining the U.S. Air Force Nuclear Mission - Snyder, Don; Nowak, Sarah; Amouzegar, Mahyar A.; Kim, Julie; Mesic, Richard (RAND Corporation, 2023)
The U.S. Air Force has prioritized the reinvigoration and strengthening of its nuclear enterprise. However, there are inherent challenges to sustaining the capabilities of nuclear systems of systems. Perhaps the most pressing challenge currently facing the Air Force nuclear enterprise is budgetary constraints. This report outlines a double-layered framework for integrating and managing the sustainment activities of the U.S. Air Force nuclear enterprise in the face of reduced funding and a smaller force structure.